Seismic damage assessment of Nepalese cultural heritage building and seismic retrofit strategies: 25 April 2015 Gorkha (Nepal) earthquake. (May 2018) - Pan, Yi; Wang, Xiaoyue; Guo, Rui; Yuan, Shuang
Abstract: The 2015 Gorkha (Nepal) earthquake caused tremendous damage to the cultural heritage buildings in the Kathmandu Valley. After the event, extensive field investigations were conducted to assess the seismic damages to the cultural heritage buildings in the Kathmandu, Patan, and Bhaktapur Durbar Squares. Major damages included failure of structural and non-structural components, tilting and collapse. Masonry-timber structures and masonry structures, the two structural types for the investigated heritage buildings, are analyzed separately in terms of the damage patterns. Damage classification criteria are proposed for the two structural types. Based on the criteria, a total of 68 structures investigated (52 masonry-timber and 16 masonry structures) are classified into four damage grades. The results show that only 30.8% of the masonry-timber structures and 18.8% of the masonry structures exhibited negligible to slight damage; the rest suffered more severe damage or even collapse. The seismic performance of the masonry-timber structures was slightly better than that of the masonry structures. Seismic retrofit strategies are recommended for the preservation of Nepalese cultural heritage buildings. Highlights: Field investigations were conducted to assess the seismic damages to the cultural heritage buildings in Nepal after the 2015 earthquake. Damages to the investigated buildings mainly included delamination and shear failure of walls, damage to columns and struts, tilting and (partial) collapse of the structure. Based on the importance of individual member to the seismic performance of the overall structure, damage classification criteria are proposed for both masonry-timber structures and masonry structures. The investigated cultural heritage buildings are classified in accordance with the criteria. The investigation results show that relative to the masonry structures, more masonry-timber structures suffered the seismic damage, but with a smaller portion exhibiting severe damage. To preserve the cultural heritage buildings, seismic retrofit strategies are recommended, including improvement of structural integrity and reinforcement of individual components (walls, grade beams, floor and roof systems). More research is needed to explore innovative ways to improve the seismic performance of the heritage buildings with the cultural attributes remained.